The relationship between carpal tunnel syndrome, smartphone use, and addiction: A cross-sectional study - Karacorlu, Fatma Nur; Balgetir, Ferhat; Pirincci, Edibe; Deveci, Suleyman Erhan (Baycinar Medical Publ-Baycinar Tibbi Yayincilik, 2022)
Objectives: This study aims to investigate the use of and addiction to smartphones in individuals with and without carpal tunnel syndrome (CTS). Patients and methods: The cross-sectional study included a total of 404 participants (286 females, 118 males; mean age: 39.7 +/- 11.6 years; range, 16 to 75 years) who applied to the Neurology Department of the Firat University Faculty of Medicine, between April 2019 and October 2019. The participants were divided into two groups: 202 patients diagnosed with CTS were included in the case group, and 202 patients and their relatives who did not have hand and wrist complaints were included in the control group. The diagnosis of CTS was made by evaluating the history, physical examination, and electromyography findings. Data were collected with participant information forms and the Smartphone Addiction Scale. Results: It was found that the risk of CTS increased 1.022 times with a one-unit increase in the SAS score and 1.292 times with a 1-h increase in daily smartphone use. Conclusion: Smartphone addiction can be considered as a potential risk factor for CTS; however, the effect of smartphone addiction on CTS severity was not examined in this study. The relationship between disease severity, smartphone use, and smartphone addiction in CTS patients requires further investigation to provide clarification on this issue.
Keywords: Electromyography; median nerve; neuropathy; smartphone addiction